Erratum: Geometric Approach to Predator-Prey Model with Carrying Capacity on Prey Population - Marshellino; Tasman, Hengki; Rusin, Rahmi (Communication in Biomathematical Sciences, 2025)
This erratum addresses inaccuracies found in the figure captions of the article titled "Geometric Approach to Predator-Prey Model with Carrying Capacity on Prey Population" [Marshellino, Tasman, H. and Rusin, R., Communication in Biomathematical Sciences, 7(2), pp. 162-176, 2024. DOI: 10.5614/cbms.2024.7.2.1].